Pengaruh Modifikasi Media Arang Sekam dan Pemberian Teh Kompos terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Krisantus Tri Pambudi Raharjo; Remigius Takaeb (Fakultas Pertanian, Universitas Timor, 2020)
Husk charcoal has an important role as a planting medium to replace soil. The husk charcoal is porous, light, not dirty and sufficient to hold water. The effect of rice husk charcoal produces a higher fruit weight and number of fruit per crop. Besides that, husk charcoal can have a good effect on soil physical properties, soil chemistry, and soil biology. The advantage of husk charcoal is that it can neutralize the pH of the soil, which is used in large quantities, even in organic agriculture the main source comes from husk charcoal and increases soil porosity, which directly increases the availability of ground water. Tea compost has several advantages and is a natural fertilizer product that is environmentally friendly, able to suppress the growth of pathogenic bacteria contained in the compost. Besides being a natural fertilizer, compost tea can also function as a natural pesticide, because tea compost can restore soil fertility naturally and increase plant resistance to pests and diseases. In addition to increasing the nutrient content of the soil, the application of tea compost can also increase the population of microorganisms which are useful for increasing soil fertility. Application on leaves, can suppress the development of pathogens that cause leaf disease. The research objective was to determine the effect media modification of husk charcoal on the growth and yield cayenne pepper and to determine the effect compost tea on the growth and yield cayenne pepper. This research was conducted in KM 9, Sasi Village, Kota District, North Central Timor Regency (TTU). Field research used a 3×3 factorial completely randomized design (CRD) repeated 3 times. The first factor is the modification of the planting media, namely; groundless, semicircular ground cover on polybag surface, full ground cover. The second factor was the spraying of compost tea, namely; without giving tea, gamal compost tea, guano compost tea. Thus obtained 9 treatment combinations that were repeated 3 times so that there were 27 experimental units. The results showed that the highest moisture content and neutral soil pH, highest plant height, largest stem diameter, heaviest plant dry weight, highest number of fruit crops, heaviest fruit weight, and heaviest plant dry weight were obtained from giving guano compost tea and full ground cover.